1992
DOI: 10.1021/bi00119a020
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin conformational studies with mixed-chain unsaturated phospholipid bilayer systems

Abstract: The transition of gramicidin from a nonchannel to a channel form was investigated using mixed-chain phosphatidylcholine lipid bilayers. Gramicidin and phospholipids were codispersed, after removal of the solvents chloroform/methanol or trifluoroethanol which resulted in nonchannel and channel conformations, respectively, as confirmed using circular dichroism (CD). The fluorescence emission maxima of the nonchannel form were shifted toward shorter wavelengths by heating at 60 degrees C (for 0-12 h), which conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
39
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 35 publications
11
39
0
Order By: Relevance
“…In both lipid preparations gramicidin is more effective when added to the liposomes from a solution in dimethylsulfoxide than from a solution in ethanol. This observation agrees with the conclusion that addition to lipid bilayers of gramicidin dissolved in dimethylsulfoxide or ethanol resulted in channel and non-channel conformations, respectively [23].…”
Section: Effect Of Uncouplers and Ionophores In Liposomes From E Colsupporting
confidence: 91%
“…In both lipid preparations gramicidin is more effective when added to the liposomes from a solution in dimethylsulfoxide than from a solution in ethanol. This observation agrees with the conclusion that addition to lipid bilayers of gramicidin dissolved in dimethylsulfoxide or ethanol resulted in channel and non-channel conformations, respectively [23].…”
Section: Effect Of Uncouplers and Ionophores In Liposomes From E Colsupporting
confidence: 91%
“…These spectra changes are caused by the changes of the tryptophan microenvironment, particularly indole side chains, during the conformational transitions in gramicidin A as it gradually converts from a double-stranded helix to a singlestranded helical dimer. 20 This result is in agreement with the previous study of monitoring the gramicidin A conformation in lipids, in which the fluorescence wavelength at 335 nm also was shown to shift to longer wavelengths. 28 Figure 2 shows representative plots of the fluorescence intensity at 335 nm against incubation time at 808C for four different molar ratios of DMPC/gramicidin A.…”
Section: Resultssupporting
confidence: 93%
“…18 The rate of transition from the double-stranded helix to the single-stranded helical dimer depends on the lipid head group, acyl chain length, and unsaturated content. [19][20][21][22][23] Two models of this conformational change have been proposed. In the ''zipper'' mechanism, the intertwined chains unscrew in opposite directions by progressively shifting the antiparallel chains past each other.…”
Section: Introductionmentioning
confidence: 99%
“…2. The emission maximum of channel formation was in agreement with the previously reported literature [15,37]. From the results it was observed that the emission maximum wavelength of channel form of gramicidin b 6.3 -helical conformation remains almost constant, i.e.…”
Section: Fluorescence Characteristics and Quenching Of Channel Form Osupporting
confidence: 91%
“…In channel conformation, the gramicidin exists as characteristic single-stranded b 6.3 helical conformation having typical peaks of positive ellipticity around 218 and 235 nm, with a valley around 230 nm and negative ellipticity below 208 nm [12,37,38]. Fig.…”
Section: Gramicidin Conformation In Membranes Monitored By Circular Dmentioning
confidence: 99%